Northwest history. Mining. Mills & mining. 1934-10-22 (1934)
Plan cyanide mill at Little Rockies Little Rockies Mining company plans a 22-ton cyanide mill at its property on Beaver creek, Phillips county, Mont., one of the old placer districts of the state. The company has two bodies of gold ore opened by a tunnel and shipments of crude ore are to start in a few days.